Attracting terrific people [soundrecording] - Glass, Lillian (Audio Renaissance Tapes, 1997)
Discusses skills and techniques to overcoming shyness and insecurity, eliminating depression, boredom and loneliness, discovering new ways of communicating. It gives a glimpse of how to begin, build, and if necessary end relationships.